Resource recovery from municipal solid waste by mechanical heat treatment: An opportunity - Kamaruddin M.A.; Yusoff M.S.; Ibrahim N.; Zawawi M.H. (American Institute of Physics Inc., 2023)
Municipal solid waste (MSW) stream in Malaysia consists of 50 to 60 % of food wastes. In general, food wastes are commingled in nature and very difficult to be managed in sustainable manner due to high moisture content. Consequently, by dumping food wastes together with inert wastes to the landfill as final disposal destination incurs large space area and reducing the lifespan of landfill. Therefore, certain fraction of the MSW as such; food wastes (FW) can be diverted from total disposal at the landfill that can improve landfill lifespan and environmental conservation. This study aims to determine the resource characteristics of FW extracted from USM cafeteria by means of mechanical heat treatment in the presence of autoclaving technology. Sampling of FW were conducted by collecting FW samples from disposal storage at designated area within USM campus. FW characteristics was performed prior and autoclaving process. The results have demonstrated that bones fraction was the highest followed by vegetable and rice with 39, 27 and 10%, respectively. Meanwhile, based on autoclaving technique, moisture content of the FW (fresh waste) were able to be reduced ranging from 65-85% to 59-69% (treated waste). Meanwhile, chemical characteristics of treated FW results in pH, TOC, TKN, C/N ratio, TP, and TK 5.12, 27,6%, 1.6%, 17.3%, 0.9% and 0.36%. The results revealed that autoclaving technology is a promising approach for MSW diversion that can be transformed into useful byproducts such as fertilizer, RDF and recyclable items. 2017 Author(s).